DIVERSITY AND MULTICULTURAL - Islam, Muhammad Hifdil (Humanistika : Jurnal Keislaman, 2017)
Abstract:Â multiculturalism recognize and respect diversity, because deviersity is part of multiculturalism. It carries the implication being that the social reality in which highly polymorphic or compound will not be an obstacle to building the social relationship between individuals with tolerance. In fact, will grow up accepting the reality for peaceful coexistence (peace co-existence) of each other with the differences inherent in every social and political entities. Thus, it can be affirmed that multiculturalism is a concept that wants to bring the community in harmony and peace, without conflict and violence, despite the complexity in which there is a difference.Â Key word: multiculturalism and diversityÂ